Novel scanned beam millimeter-wave antenna using micromachined variable capacitors on coplanar structures - Hamdi, A.; Samet, A. (Journal of Digital Information Management, 2011)
This paper presents a new approach of modelling, design, and characteristics of variable radio frequency microelectromechanical system (RF-MEMS) capacitor integrated on leaky wave antenna (LWA) operating at 94 GHz. This antenna was implemented on grounded coplanar waveguide (CPW). A 2D distributed mathematical model for the capacitor has been developed alongthis paper; we formulate and solve the static and dynamic problems associated with the proposed RF-MEMS capacitor. The obtained results are in good agreement with the ANSYS simulations. A full-wave simulation was used to investigate the microwave performances of the proposed antenna. This prototype exhibits continuous tuning radiation angle and beamwidth capability by tuning bias voltages from 0 V to 60 V. The proposed antenna presents flexibility, high directivity, compact size, and low-cost characteristics. The LWA can be used in applications which require high-performance such as imaging arrays and collision-avoidance radars.
Keywords: CPW; DQM; LWA; MEMS; Millimeter-waves; Surface micromachining